Association between normative and perceived esthetic results after treatment of mandibular retrognathism - MARQUES,Glauco André (2019)
Abstract Introduction This cross-sectional study aimed to associate the normative cephalometric results of mandibular retrognathism treatment with patient perception on the esthetic improvement of facial profile. Objective this cross-sectional study aimed to associate the normative cephalometric results of mandibular retrognathism treatment with patient perception on the esthetic improvement of facial profile. Material and method The normative cephalometric results were obtained from lateral cephalometric radiographs of a sample of 24 Class II malocclusion patients in the pubertal growth spurt. Such patients were treated with a mandibular advancement device and evaluated by comparing pre- and post-treatment variables. The same radiographs were used to produce standardized black silhouettes that were randomly arranged. Patients were instructed to choose their preferred profile and indicate the changes perceived using a 7-point Likert scale. The data were compared with cephalometric results using a mixed-model methodology for time-repeated measures, Student’s t-test, and t-test for heterogeneous variances, at 5% significance level. Result A rate of 75% of patients preferred post-treatment silhouettes and changes were perceived regardless of the choice of either pre- or post-treatment profile. There was no significant difference between the cephalometric variables of the tracings that produced the silhouettes considered better or worse after the evaluation. Conclusion There was no association between the cephalometric results after treatment and the perception of esthetic improvement by patients treated for mandibular retrognathia.